Preliminary evaluation of eyestalk ablation and thoracic ganglion importation on spermatophore quality and molting of male Penaeus vannamei - Alfaro-Montoya, Jorge (1992)
Males of Penaeus vannamei (mean weight = 25.05 ± 1.89 g), selected from a commercial semi-intensive pond, selected form a commercial semi-intensive pond, were used to study the effect of thoracic ganglion implantation on spermatophore quality, and the effect of eyestalk ablation on molt cycle duration. Thoracic ganglion implantation did not benefit spermatophore sperm count and spermatophore weight, whereas eyestalk ablation significantly (P<0.05) improved spermatophore quality. Eyestalk ablation did not shorten molt cycle duration. It is believed that eyestalk ablation has a different effect and molting depending on the natural environment of each species.